LPS-Challenged Macrophages Release Microvesicles Coated With Histones - Nair, Rohini Ravindran; Mazza, Davide; Brambilla, Francesca; Gorzanelli, Andrea; Agresti, Alessandra; Bianchi, Marco E. (Frontiers in Immunology, 2018)
Histones are the protein component of nucleosomes, which are the basic packing unit of chromatin. However, histones are also found in the blood, both as components of nucleosomes leaked out from dead cells, or expelled from neutrophils in the active process of NET formation. Circulating histones contribute to inflammation, and to lethality in sepsis, a hyperinflammatory condition, by interacting with specific receptors, notably toll-like receptor 4 (TLR4). Here, we show that histones are also actively released by LPS-activated macrophages in association with extracellular vesicles. Vesicle-associated histones can be recovered from the plasma of mice with sepsis. Actively released histones are on the outer surface of vesicles and can interact with TLR4. Thus, activated macrophages release histones without dying, at the same time, making their DNA more accessible and communicating to other cells that infection is present.